Doping Effect on the Structural Properties of Zno: Al2O3 Thin Films by Pulsed Laser Deposition - Yousif, Ali A; Habubi, Nadir F; Haidar, Adawiya J (Al-Nahrain Journal of Science, 2018)
Polycrystalline Alumina-doped Zinc Oxide (AZO) thin films on glass substrates have been deposited by pulsed laser deposition technique using pulsed Nd-YAG laser with wavelength (λ= 532 nm) and duration (7ns). The structural properties of these films were characterized as a function of Al2O3 content (1 w.t%, 3 w.t% and 5 w.t %) in the target at substrate temperatures (200°C and 400°C) and energy fluence (0.4 J/cm2). The X-ray diffraction patterns and scanning electron microscopy (SEM) for the films showed that the undoped and Al2O3-doped ZnO films exhibit hexagonal wurtzite crystal structure and high polycrystalline quality with a preferred orientation along (100) plane. The grain size increases as the Al2O3 concentration increases to 85.6 nm. The surface morphology of the films obtained by scanning electron microscopy reveals that presence of Al2O3 content in the structure did affect the surface morphology of the films significantly.